Pengaruh Penerapan Model Pembelajaran Sentra Persiapan Terhadap Perkembangan Berpikir Simbolik - Maryati, Mira; Yulianingsih, Yuyun; Nurdiansah, Nano (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
The research is phenomena where there are gaps in the application of the preparatory center learning model which seems saturated tends to use daily worksheets. Not a few children who are low in the ability to think symbolically in recognizing concept of symbols, letters and numbers. Not yet sensitive to the sound of letters and cannot interpret it in written form. This study aims to determine 1) the level of development of children's symbolic thinking in the experimental class using the preparatory center learning model; 2) the level of development of symbolic thinking in the control class using the group learning model; 3) the difference between the experimental and control classes. The research method uses a quasi-experimental. Subjects were 31 children. Data collection techniques through interviews and observation. Data analysis using partial analysis, normality test, homogeneity and hypothesis. The results development of symbolic thinking experimental class children obtained pre-test score of 57.70 with less qualification and a post-test of 80.8 with very good qualifications. while the control class obtained pre-test score of 57.45 with poor qualifications and a post-test of 75.13 with good qualifications. the difference of 79.8% and remaining 20.2% is influenced by other factors. The results of hypothesis test significance level of 5% tcount=2.847>ttable=2.045. So it is interpreted that Ha is accepted and H0 is rejected, meaning that there is a significant difference between development of children's symbolic thinking through reparatory center learning model and group learning model in class B RA Persis 235 Nasrullah Ujungberung Bandung City